Effect of Semisolid Formulation of Persea Americana Mill (Avocado) Oil on Wound Healing in Rats. (19th March 2013) - de Oliveira, Ana Paula; Franco, Eryvelton de Souza; Rodrigues Barreto, Rafaella; Cordeiro, Daniele Pires; de Melo, Rebeca Gonçalves; de Aquino, Camila Maria Ferreira; e Silva, Antonio Alfredo Rodrigues; de Medeiros, Paloma Lys; da Silva, Teresinha Gonçalves; Góes, Alexandre José da Silva; Maia, Maria Bernadete de Sousa
Abstract : The aim of this study was to evaluate the wound-healing activity of a semisolid formulation of avocado oil, SSFAO 50%, or avocado oil in natura, on incisional and excisional cutaneous wound models in Wistar rats. An additional objective was to quantify the fatty acids present in avocado oil. On the 14th day, a significant increase was observed in percentage wound contraction and reepithelialization in the groups treated with 50% SSFAO or avocado oil compared to the petroleum jelly control. Anti-inflammatory activity, increase in density of collagen, and tensile strength were observed inSSFAO 50% or avocado oil groups, when compared to control groups. The analysis of the components of avocado oil by gas chromatography detected the majority presence of oleic fatty acid (47.20%), followed by palmitic (23.66%), linoleic (13.46%) docosadienoic (8.88%), palmitoleic (3.58%), linolenic (1.60%), eicosenoic (1.29%), and myristic acids (0.33%). Our results show that avocado oil is a rich source of oleic acid and contains essential fatty acids. When used in natura or in pharmaceutical formulations for topical use, avocado oil can promote increased collagen synthesis and decreased numbers of inflammatory cells during the wound-healing process and may thus be considered a new option for treating skin wounds.